Pengelolaan Konservasi Penyu Sebagai Daya Tarik Wisata Di Pantai Kuta - Febryanus Orlando Yoni Uskono; I Gede Anom Sastrawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2022)
This study aims to determine the management of turtle conservation as a tourist attraction onKuta Beach which is in a mass tourism area so it does not threaten the existence of turtle species that laytheir eggs on Kuta Beach. How is the development of turtle conservation as a tourist attraction on KutaBeach that pays attention to the balance between natural resources and tourism activities on KutaBeach.The type of data used in this study are primary and secondary data types. Data collectiontechniques used in this study were observation, in-depth interviews, and documentation. The technique ofdetermining informants using purposive sampling. While the data analysis technique uses descriptivequalitative analysis.The results of research conducted that the management of sea turtles conservation as a touristattraction in Kuta Beach is very unique for domestic and foreign tourists because it is located in the masstourism area. However, conservation support facilities are inadequate and the need for collaborationbetween stakeholders, namely the government, non government organization and the community topreserve sea turtles in Kuta Beach from the threat of garbage and wild animals.Keywords: Conservation Management, Sea Turtles, Kuta Beach